Gene cloning and functional study of PmKSPI from Pinctada fucata martensii. Issue 131 (December 2022) - Shen, Chenghao; Zhang, Meizhen; Liang, Haiying; He, Junjun; Zhang, Bin; Liang, Bidan
Abstract: Kunitz-type serine protease inhibitors (KSPI) are a family of serine protease inhibitors (SPIs) and are extensively found in animals, plants, and microbes. SPI can inhibit proteases that may be harmful or unwanted to its cells. Here, a four-domain Kunitz-type SPI, PmKSPI, was cloned by RACE in the pearl oyster Pinctada fucata martensii . The full-length cDNA sequence of PmKSPI was 1318 bp, including the 5′ UTR (25 bp), the 3′ UTR (96 bp) and ORF (1197 bp). Homology analysis indicated that PmKSPI had the highest resemblance (30.14%) with its homolog in Crassostrea gigas . Phylogenetic analysis revealed that PmKSPI clustered with homologs in other molluscs. We found that PmKSPI mRNA expression in P. f. martensii was distributed in all six tissues, with the highest level in the mantle, and almost no expression in other tissues. After PAMPs challenge, expression of PmKSPI mRNA in the mantle was significantly up-regulated. The recombinant protein rPmKSPI significantly inhibited the growth of 5 kinds of Gram-negative bacteria but had little effect on Gram-positive bacterial activity. Transmission electron microscopy showed that plasmolysis occurred in two Gram-negative bacteria species when treated with rPmKSPI. rPmKSPI may thus have a bactericidal effect by destroying the bacterial cell membrane or cell walls and releasing its contents. Therefore, our results suggest that PmKSPI is tightly associated with the immunological defence of P. f. martensii . Highlights: A novel Kunitz-type serine protease inhibitors ( PmKSPI ) was identified from Pinctada fucata martensii. The mantle is the main tissue for PmKSPI expression and PmKSPI was significantly up-regulated after PAMPs induction. rPmKSPI showed antimicrobial activities against 5 kinds of Gram-negative bacteria. The mode of action of rPmKSPI on bacteria is the lysis of membrane type.